Designing An Application of Software Project Management By Using Framework Scrum (SPM-Scrum) - Santoso, Nurudin; Amalia, Faizatul (Journal of Information Technology and Computer Science, 2021)
Most of failures of startup application in many countries reached 75%, while the startup failures in Indonesia reached 90%. These failures were caused by non-technical or management factors in managing startup. The RPL (Software Engineering) Laboratory of FILKOM of Brawijaya University has a roadmap to develop an application to guarantee the success of a management software project. The data analysis had been performed on FILKOM student’s thesis work which generally develops software that has main obstacle in the management. A study solution which was developed through scientific SDLC and PMLC combined with Scrum method becomes an application named SPM-SCRUM. The results of analysis carried out on several software development projects refer to the Iterative SDPM process. Furthermore, the strategy of Iterative SDPM combined with Scrum method produces a system architecture design that separates the Front End and Back End